Demonstration versus actual student performance of chemistry experiments - Calaor, Rose Eden T. 1953- (1986)
The study was undertaken to compare the effects of student's performance of laboratory activities and student/teacher demonstration on achievement, retention and attitudes of students in Chemistry.
Vita.
Thesis (M.A.T.)--University of the Philippines, Diliman.
Keywords: Chemistry -- Study and teaching (Secondary).; Chemistry -- Experiments